Molecular Structure and Vibrational Assignment of 2-,4-,6-Methylquinoline by Density Functional Theory (DFT) and Ab Initio Hartree-Fock (HF) Calculations - Özel, Ayşen E.; Kecel Gündüz, Serda; AKYÜZ, SEVİM (Elsevier, 2006)
The molecular geometry, the normal mode frequencies and corresponding vibrational assignments of 2-,4-,6-methylquinoline (2-,4-,6-mq) in the ground state were performed by HF and DFT/B3LYP levels of theory using the 6-31++G(d,p) basis set. Harmonic and anharmonic vibrational frequencies were calculated. The complete assignments were performed on the basis of the total energy distribution (TED) of the vibrational modes, calculated with scaled quantum mechanics (SQM) method by using parallel quantum mechanic solutions program. The general agreements between the observed and calculated frequencies are shown.
Keywords: Ab Initio Calculations; Hartree-Fock; DFT; Quinaldine; 2-,4-,6-Methylquinoline; Vibrational Frequencies